Strengthening Youths’ Morals Through Character School - Khusnah, Lailatul; Al Rasyid, Harun (Tadibia Islamika: Journal of Holistic Islamic Education, 2023)
This study investigates the effectiveness of character schools (known as "sekolah karakter or sekuter") in instilling moral values in adolescents, particularly in the context of today's technology-driven world where children can easily access information independently, including content that may not be suitable for their age. Iqro Club is an institution dedicated to religious and social activities, providing a platform for positive engagement, skill development, and the cultivation of a respectful and virtuous Muslim identity among adolescents. The research problem addressed in this study revolves around understanding how character schools (sekuter) contribute to moral reinforcement in adolescents. The primary objective is to assess the practical implementation of moral strengthening through character schools (sekuter). This research adopts a qualitative approach, employing a case study research design, and is conducted at Iqro Club in Pekalongan Regency. Data collection methods encompass observation, interviews, and document analysis, while data analysis involves data reduction, presentation, and drawing conclusions. The study findings reveal three key stages: planning, implementation, and evaluation. During the planning phase, Iqro Club formulates a tailored lesson plan and curriculum that align with the specific needs of adolescents. The implementation phase adheres to established standards, including opening procedures, Quran recitation, content delivery, discussions, and concluding activities. Importantly, the content and discussions are strategically designed to address moral indicators. Finally, in the evaluation phase, participants are required to complete a daily checklist to assess their progress and engagement in the character school program.